A smart catalyst system for the valorization of renewable furfural in aliphatic alcohols. Issue 4 (5th October 2015) - Liu, Zonghui; Tong, Xinli; Liu, Jinbiao; Xue, Song
Abstract : A highly efficient and selective oxidative condensation–hydrogenation process of renewable furfural with aliphatic alcohols mediated by supported Pt catalysts in a one-pot reactor is developed. Abstract : A highly efficient and selective oxidative condensation–hydrogenation process of renewable furfural with aliphatic alcohols catalyzed by metallic platinum in a one-pot reactor is developed. A series of supported platinum catalysts including Pt/FH, Pt/H, Pt/HT, Pt/Fe3 O4, Pt/Al2 O3 and Pt/ZrO2 are prepared and employed for the polarization of furfural in ethanol and n -propanol. It is found that, in the presence of Pt/FH and potassium carbonate, 93.9% conversion of furfural and 67.9% selectivity to furan-2-acrolein were obtained via oxidative condensation in the furfural–ethanol–O2 (FEO) system, and 90.1% conversion of furfural and 90% selectivity to 3-(furan-2-yl-)-2-methylacrylaldehyde were obtained via oxidative condensation in the furfural– n -propanol–O2 (FPO) system. Moreover, the oxygen in the FPO system is completely replaced by molecular hydrogen to allow the further conversion of 3-(furan-2-yl-)-2-methylacrylaldehyde, while the catalytic system was kept unchanged. During this process, 87.3% conversion of 3-(furan-2-yl-)-2-methylacrylaldehyde and 73.2% selectivity to 3-(furan-2-yl-)-2-methylpropanol were obtained via a hydrogenation reaction with the Pt/FH catalyst. Moreover, several common bases as promoters were investigated in detail. All the catalysts were characterized by XRD, TEM, SEM, TPD and BET methods to reveal their catalytic nature in the reaction.